2019
DOI: 10.1111/gcb.14892
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐driven habitat change causes evolution in Threespine Stickleback

Abstract: Climate change can shape evolution directly by altering abiotic conditions or indirectly by modifying habitats, yet few studies have investigated the effects of climate‐driven habitat change on contemporary evolution. We resampled populations of Threespine Stickleback (Gasterosteus aculeatus) along a latitudinal gradient in California bar‐built estuaries to examine their evolution in response to changing climate and habitat. We took advantage of the strong association between stickleback lateral plate phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 65 publications
(125 reference statements)
0
26
0
Order By: Relevance
“…We further propose that in the case of populations reduced to unusually small body sizes, like those in acid lochs, complete loss of pelvic apparatus, spines and lateral plates appears to be favoured under selection as a mechanism to further reduce friction drag and thereby maintain sufficiently rapid escape responses to enable fish to avoid predators. An implication of our findings is that elevated temperatures will tend to shift selection pressures on stickleback plate morph, potentially driving plate loss (Des Roches et al , ). As such, stickleback lateral plate phenotype offers a powerful tool for monitoring change in climate variables.…”
Section: Discussionmentioning
confidence: 78%
“…We further propose that in the case of populations reduced to unusually small body sizes, like those in acid lochs, complete loss of pelvic apparatus, spines and lateral plates appears to be favoured under selection as a mechanism to further reduce friction drag and thereby maintain sufficiently rapid escape responses to enable fish to avoid predators. An implication of our findings is that elevated temperatures will tend to shift selection pressures on stickleback plate morph, potentially driving plate loss (Des Roches et al , ). As such, stickleback lateral plate phenotype offers a powerful tool for monitoring change in climate variables.…”
Section: Discussionmentioning
confidence: 78%
“…Experimental studies confirm that higher plate numbers allow increased survival during encounters with predatory fishes including salmonids (Reimchen 1991(Reimchen , 1992(Reimchen , 2000. Variation at the Ectodysplasin-A (Eda) locus explains 75-80% of the variation in plate number (Colosimo et al 2004, Kitano et al 2008, Des Roches et al 2020. Individuals with two copies of the low allele (L) tend to have few plates (<10), those with two copies of the complete allele (C) tend to have a continuous row of plates (>30 in some populations), and heterozygotes are more variable but generally have an intermediate phenotype or look like homozygous completes (Colosimo et al 2005, Miller et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Selection against low plates from fish predators may be relaxed if those fish predators prefer open water habitats and are less dense in the vegetated habitat. A study across the whole state of California found that higher frequencies of low plate morphs in estuaries that had lower proportions of flowing riverine wetlands and more lotic habitat (Des Roches et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The threespine stickleback (Gasterosteus aculeatus) is a model vertebrate in behavioral and evolutionary biology that possesses these features and is widely distributed across the northern hemisphere. The species occupies a wide range of environments and shows a high degree of phenotypic variability over small spatial scales (Bell & Foster 1994;Wootton 1976Wootton , 1984Wootton , 2009Des Roches et al 2019;Smith et al 2020a). Marine populations of the threespine stickleback have repeatedly invaded freshwater habitats.…”
Section: Introductionmentioning
confidence: 99%
“…A number of hypotheses have been proposed to explain the selective agent responsible for armor loss in freshwaters, including predation, calcium and phosphorus availability, water density, parasitism, competition, body size and swimming performance (Wootton 2009;Myhre & Klepaker, 2009;Barrett, 2010;Smith et al 2020b). At a large geographic scale, it is also apparent that temperature plays a role in driving variation in lateral plate number (Münzing 1963;Wootton 1976Wootton , 1984Des Roches et al 2019;Smith et al 2020b), with well-developed armor associated with low winter temperatures and the converse at higher temperatures. A striking deviation from the typical pattern of lateral plate morph evolution is the widespread occurrence of fully plated sticklebacks in fresh waters in eastern Europe and the east coast of North America, where they are associated with low winter temperatures (Wootton, 1976(Wootton, , 2009Hagen & Moodie, 1982).…”
Section: Introductionmentioning
confidence: 99%